2012
DOI: 10.1002/j.0022-0337.2012.76.6.tb05314.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching, Research, and Job Satisfaction of Prosthodontic Faculty Members in Indian Academic Dental Institutions

Abstract: The aim of this study was to determine prosthodontic faculty members' satisfaction with their roles of teaching, research, and service in academic dental institutions of India. The head of the prosthodontic department of each institution was informed of the study by telephone and asked to invite his or her staff members to complete a questionnaire. The questionnaire used a rating scale of 1=very dissatisied, 2=dissatisied, 3=neutral, 4=satisied, and 5=very satisied. The satisfaction score for each of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Most of the prosthodontic academic faculty members in India gave neutral responses regarding financial support for research and institutional research rewards. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the prosthodontic academic faculty members in India gave neutral responses regarding financial support for research and institutional research rewards. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…most of the prosthodontic faculty members in India were satisfied with teaching and service items, but were rather dissatisfied with the financial and academic support for preparing presentations and attending conferences. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…This will improve and maintain the liveliness of academics and will prepare successfully, the future generation of academic faculty. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that opportunities to participate in new developments outside the home institution is another important factor infl uencing academic job satisfaction. 4 RN has been actively involved in the local dental society, and has served on many committees. These commitments can confl ict with teaching duties; however, the leadership has been supportive to allow the deferment of those responsibilities.…”
Section: Encourage Participation In External Professional Opportunitiesmentioning
confidence: 99%
“…An Indian study of dental academics identifi ed that the freedom to select and decide curriculum content and the opportunity to construct exams were important factors for job satisfaction. 4 Additionally, junior faculty members should be invited to serve on important boards and committees. Service on committees allows for a deeper understanding of institutional operations, challenges and opportunities.…”
Section: Allow Service On Important Boards and Committeesmentioning
confidence: 99%